(untitled) (Semiárida, 2020)
In the Caldenal region, livestock grazing occurs mainly in large areas with a single watering point thus favoring the formation of piospheres (gradients of grazing pressure). The objectives of this study were (i) to examine the density, cover, depth of the resprouting buds and the seed bank of Piptochaetium napostaense and Poa ligularis in relation to the distance to the watering point, and (ii) to investigate if the grazing pressure differentially affected these two perennial bunchgrasses. Results showed that the cover of P. napostaense is affected by the distance to the water source whereas no effects were observed in the cover of P. ligularis. The density of P. napostaense was higher in the area of intermediate grazing pressure. A detrimental effect of cattle grazing and trampling was observed in the proximity to the watering point where the seeds of P. napostaense showed the lowest germination values. Nevertheless, no seeds of P. ligularis were observed in the collected samples. Overall, it appears that the gradient of grazing pressure produces different responses in the populations of P. ligularis and P. napostaense.